Specificities of Scanning Electron Microscopy and Histological Methods in Assessing Cell-Engineered Construct Effectiveness for the Recovery of Hyaline Cartilage - Mikhail S. Bozhokin; Svetlana A. Bozhkova; Aleksandr A. Rubel; Julia V. Sopova; Yulia A. Nashchekina; Natalya B. Bildyug; Mikhail G. Khotin (Methods and Protocols, 2021)
Damage to the hyaline layer of the articular surface is an urgent problem for millions of people around the world. At present, a large number of experimental methods are being developed to address this problem, including the transplantation of a cell-engineered construct (CEC) composed of a biodegradable scaffold with a premixed cell culture into the damaged area of the articular surface. However, current methods for analyzing the effectiveness of such CECs have significant limitations. This study aimed to compare the SEM technique, classical histology, and cryosectioning for the analysis of CECs transplanted to hyaline cartilage.